History : past, present and future book 1 - Jackson, Michael, 1958-2009; MJJ Productions; Sony Music Entertainment (Malaysia). (New York : MJJ Productions, 1995)
Contains five tracks taken from History album.
CD 1 : They Don't Care About Us / (4:44) -- You Are Not Alone / (5:45) -- 2 Bad / (4:49) -- Stranger In Moscow / (5:44).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Popular music